Letter from Charles Coulson to Harrison Shull, 1958 - Coulson, C. A. (Charles Alfred) (1958)
Concerns receipt of reprint sent to Coulson by Shull.
Keywords: Hydrogen; Shull, Harrison; Mathematicians; Chemists; Helium; Quantum chemistry; Coulson, C. A. (Charles Alfred), 1910-1974